Perbandingan Karakteristik Biodegradable Foam dari Pati Ubi Jalar dan Pati Kentang dengan Penambahan Serat Selulosa - Hana Isabella; Nanik Hendrawati (Jurnal Ilmiah Teknik Kimia, 2022)
Biodegradable foam is an alternative to styrofoam which is made from starch raw materials that can be degraded by nature. However, the starch-based biodegradable foam has weaknesses in water absorption and tends to be fragile so special applications are needed to able to increase strength, elasticity, and resistance to water. Therefore, the filler is added in the form of cellulose fibers derived from banana stems which have a large cellulose content and little lignin, to increase cellulose content, the cellulose isolation stage is carried out. This study aims to determine the effect of adding cellulose fibers to biodegradable foam made of two different types of starch on the characteristics of biodegradable foam. The manufacture of biodegradable foam is carried out by the baking process method and uses two different types of starch as the main ingredients, namely sweet potato starch and potato starch. The added cellulose fibers varied from 1%, 3%, 5%, 7%, and 9% w/w by weight of starch. The results of testing biodegradable foam from two different types of starch show that the absorption capacity using potato starch with variable cellulose is 9% lower than foam with sweet potato raw materials. The biofoam that has the greatest biodegradability value is the sweet potato starch biofoam at a variable of 9% cellulose fiber. Biodegradable foam made from sweet potatoes with a cellulose variable of 9% has the highest tensile strength value of 11,221 MPa.